1. 3х - 3
2. -11
3. 7х - 1
4. -20
5. 5
6. 2х - 9
7. 2
8. 7х - 10
9. -19
10. 7х - 5
Объяснение:
1. 3(х+4) - (3-х) - х - 4 = 3х + 4 - 3 + х - х - 4 = 3х - 3
2. x + 4 - 5(2-х) - (5+1)х - 5 = х + 4 - 10 + 5х - 5х - х - 5 = 4 - 10 - 5 = -11
3. 4(x+4) - 4(3-х) - x - 5 = 4х + 16 - 12 + 4х - х - 5 = 4х + 4х - х + 16 - 12 - 5 = 7х - 1
4. x + 2 - 4(5-х) - (4+1)х - 2 = х + 2 - 20 + 4х - 4х - х - 2 = -20
5. 2(x+4) - (1-x) - (1+2)х - 2 = 2х + 8 - 1 + х - х - 2х - 2 = 8 - 1 - 2 = 5
6. x + 2 - 2(5-х) - x - 1 = х + 2 - 10 + 2х - х - 1 = 2 - 10 - 1 + 2х = -9 + 2х = 2х - 9
7. 4(x+2) - (1-x) - (1+4)х - 5 = 4х + 8 - 1 + х - х - 4х - 5 = 8 - 1 - 5 = 2
8. 4(х+2) - 4(4-x) - x - 2 = 4х + 8 - 16 + 4х - х - 2 = 4х + 4х - х + 8 - 16 - 2 = 7х - 10
9. 3(х+1) - 4(5-х) - (4+3)х - 2 = 3х + 3 - 20 + 4х - 4х - 3х - 2 = 3 - 20 - 2 = -19
10. 3(x+3) - 5(2-х) - x - 4 = 3х + 9 - 10 + 5х - х - 4 = 3х + 5х - х + 9 - 10 - 4 = 7х - 5
f(-2)= -(-2)^2+(6*(-2)-10= -4+(-12)-10=-26
f(2)= -(2^2)+ 6*2-10= -4+12-10= -2
f(-3)= -(-3^2)+ 6*(-3)+10= -9-18-10=-37
f(5)= -(5^2) + 6*5+10= -25+30-10= -5
Объяснение: